An integrated network and storage architecture for sharing high-quality broadcast TV contents. - Kim, Eunsam (IEEE Communications magazine)
With the advent of personal video recorders (PVRs), the way people watch TV is rapidly changing. By recording or time-shifting live TV programs into the embedded-disk storage of a PVR, people can watch what they want independent of the broadcasting schedule. Furthermore, peer-to-peer networking technology provides an additional TV content distribution channel to unidirectional broadcasting. However, due to the current limited broadband bandwidth, it is difficult to support high-quality TV content streaming between PVRs on the Internet. In this article we propose novel integrated network/storage architecture to provide the streaming of high-quality broadcast TV contents over fast network connections. To take full advantage of our system resources, we also develop efficient sharing schemes such as matching of a communication pair and channel assignment for extensive time-shifting.